BIOACTIVE PEPTIDES FROM THE GRAPSID CRAB GRAPSUS STRIGOSUS (SAKAI, 1976) - e, RETHNA PRIYA; s, RAVICHANDRAN (Asian Journal of Pharmaceutical and Clinical Research, 2014)
Â  Â Objective: Antimicrobial peptides (AMPs) are small peptides existing widely in mammals, amphibians and marine invertebrates they appear to be one of the factors in innate immunity. AMPs are widely expressed in organisms and have been linked to innate and acquired immunities in marine vertebrates. Methods: An antimicrobial screening of Grapsus strigosus, a grapsid crabs hemolymph extracts were subjected to antimicrobial assay. Antimicrobial screening was done in ten consecutive human pathogenic bacterial and fungal pathogens using the standard disc diffusion method. The antibacterial test of the sample confirmed positive results against most of the pathogens used. Results: In G. strigosus, maximum effect was recorded against Vibrio cholera (8 mm) and the lowest zone of inhibition against Staphylococus aureus (2 mm). In the positive control, maximum effect was recorded against Vibrio parahemolyticus (8 mm) and the lowest zone of inhibition against Klebsiella pneumoniae (4 mm). In antioxidant assay, the percentage of 2, 2-diphenyl-1-picrylhydrazyl scavenging activity was recorded as 1.21%. The protein content was estimated as 17.2 mg/ml. In thin layer chromatography, pink spots confirmed the presence of proteins. In sodium dodecyl sulfate polyacrylamide gel electrophoresis, five bands were detected in the gel that represents the presence of proteins in the range nearly 25.6-75.8 KDa. Conclusion: The present study clearly shows that the various fractions was found to be rich in ninhydrin positive spots indicating the possibility of containing peptides, further confirmed by the presence of doublets in the region of its nuclear magnetic resonance spectrum. Hence, the present study indicated that the hemolymph of G. strigosus crabs may potential antibiotics. Keywords: Crab, Hemolymph, Anti-microbial peptide, Thin-layer chromatography, Nuclear magnetic resonance